An examination of the correlation between website traffi c and the quality of services provided by Jumia Uganda. - Ssemaluulu, Paul Mukasa; Isingoma, Fenehansi; Mugavu, George (Kabale University, 2024)
An attempt to divorce E-marketing from current business operations is a futile one worldwide presently. The two are like Siamese twins since a strong digital marketing platform benefits from current business operations very well. Website development became fundamental following the discovery of the Internet in early 1983 and the World Wide Web in 1989. It is on such background that Jumia Uganda, an online business platform was conceived. The research employed a cross-sectional survey design to investigate the association between electronic marketing efforts and service quality. A mixed-methods research approach, incorporating both quantitative and qualitative methodologies, was deemed highly relevant for this study. In addition, from the 255 target respondents, a definite sample size of 101 was determined using William G. Cochran's (1997) formula. However, just like any usual business, web-based businesses like the ones of Jumia Uganda are not short of incapacitation which among others is low website traffic which impacts the sales of such businesses directly. The paper provides a detailed literature review concentrating on the nexus between website traffic and quality services. Based on empirical evidence, we conclude that the moderate positive correlation coefficient of (r=0.390**) suggests a correlation between website traffic and service quality. As website traffic increases, there is a tendency for service quality to improve. The significance level for both correlations was 0.000, indicating that the correlation coefficients were highly significant at the 0.01 level (2-tailed). This positive correlation implies a connection between website traffic and service quality. From the empirical conclusion, we are in a position to come up with a key recommendation stating that to enhance its online presence, Jumia should consider diversifying its website content with engaging formats such as blog posts, videos, and infographics to appeal to a broader audience. Consistent updates and the regular refreshment of content are crucial for maintaining visitor interest.